Integrating Blockchain, SSI, and RBAC for the Secure Management of Defense Heritage Buildings - Gavina Baralla; Luisanna Cocco; Marco Di Francesco; Roberto Tonelli (IEEE Access)
This paper presents a Blockchain-SSI based system designed for the management and monitoring of historical heritage, with a focus on Italian defence heritage buildings. The system supports a modular architecture to integrate cutting-edge technologies, including decentralized applications managed through Smart Contracts and SSI, to enhance security, data integrity, and user autonomy in personal data management. Central to our system is the innovative dual-layer access control that combines SSI with Role-Based Access Control (RBAC), ensuring decentralized and secure management of identities and access permissions. A key component of the building system’s architecture is the blockchain module that enables the certification of data, documents or activities while offering query and verification services on this certified data. Through a detailed exploration of use-case scenarios, this paper illustrates the practical application and benefits of the system, demonstrating its potential to revolutionize heritage conservation practices. The use of Blockchain technology in this context represents an exceptional opportunity for data integrity and reliability among stakeholders, securing and tracing maintenance and processes in historic defence buildings. Additionally, the mechanism for access level control by integrating SSI and RBAC provides robust management of the system while simultaneously empowering individuals to retain control over their data.